A novel catalytic way of comprising a β-nucleating agent in isotactic polypropylene: Catalyst design strategy and polymerization-assisted dispersion. (24th March 2017) - Wang, Na; Niu, Hui; Li, Yang
Abstract: This article demonstrates a catalytic as well as efficient method to comprise a β-nucleating agent N, N '-dicyclohexyl-terephthalamide (DCTPA) into isotactic polypropylene (iPP) for the synthesis of β-crystalline-specified iPP (β-iPP). A novel DCTPA-based Ziegler-Natta catalyst was designed via a first modification step of DCTPA with TiCl4 and a subsequent supporting step of MgCl2 -TiCl4 -donor components on DCTPA, by which the final catalyst composition and morphology were facilely controlled, and the propylene polymerization was endowed with high activity as well as high stereospecificity. The chemical structure of the DCTPA supported Ti-Mg catalyst was investigated using FTIR, XPS and XRD, and the morphology of the catalyst particle and its polymers was monitored by SEM. Moreover, uniform dispersion of DCTPA fragments in iPP resin was realized through the in-reactor polymerization, benefiting from the catalyst-polymer morphological replication effect, followed by inducing the homogeneous β-modification of iPP with high efficiency after a melting-crystallization treatment of the polymers. This novel difunctional catalyst proved to be effective for both propylene isotactic polymerization and polymer β-modification. Graphical abstract: Highlights: Design and fabrication of a novel β-nucleating agent based Ziegler-Natta catalyst. In-reactor preparation of β-crystalline-specified isotactic polypropylene. Realize uniform dispersion of β-nucleator and efficient β-modification of iPP.